Pengaruh Pemberian Tunjangan Dan Bonus Terhadap Loyalitas Kerja Karyawan Pada PT. Phalosari Unggul Jaya Jombang - Rijalul Faqih Hadi; Abdul Kodir Djaelani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This research was conducted at PT. Phalosari Unggul Jaya Jombang. The purpose of this study was to examine and analyze the effect of allowances and bonuses on employee job loyality at PT. Phalosari Unggul Jaya Jombang. The variables used are allowances and bonuses as independent variables, while the employee job loyality variable is the dependent variable. The sample used in this study were 69 employees of PT. Phalosari Unggul Jaya Jombang. The sampling technique uses probability sampling. Data collection methods by collecting primary and secondary data. The analysis used includes instrument test, normality test, classical assumption test, multiple linear regression analysis, and hypothesis testing with the help of SPSS 25.0. The results showed that the variables of giving allowances and bonuses, and employee job loyality had an effect simultaneously. the variable giving allowances has a partial effect on employee job loyality, the bonus variable has a partial effect on employee job loyalityKeywords : Allowances, Bonuses and Employee Loyality